Hydrolysis of cotton fabric from hospital waste for ethanol production using sub-critical water - Abu Toat, Shamsainon (2021)
Currently in Malaysia, most wastes are disposed into poorly managed systems with little or no pollution protection measures. Large amounts of wastes such as textiles are generated through hospitals and health care centers. However, the improper management of these abundantly generated wastes may pose an environmental pollution problems and fire hazard. Cotton textile is a potential biomass for bioethanol production. Subcritical water (Sub-CW) hydrolysis was investigated as an alternative technology for the recycling of cotton textile waste for current health care waste management. The aim of this study is to investigate the possibility of complete conversion of cotton textile waste to ethanol via Sub- CW hydrolysis and fermentation. Sub-CW was carried out to facilitate the hydrolysis of cellulose component in cotton textile (cotton 75%+polyester 25%). The study was divided into two parts; (i) To evaluate the subcritical water parameters such as temperature and time to achieve maximum yield of sugars. (ii) Fermentation of the hydrolysate obtained from Sub-CW hydrolysis to ethanol. Under Sub-CW conditions of temperature (140 °C - 350 °C), reaction time (1-10 min) and water to cotton ratio (3:1) revealed that cotton textile treated at 280 °C for 4 min, was optimal for maximizing yield of sugar, which was 0.213 g/g-dry sample. The quantitative analysis by HPLC showed that the soluble carbohydrates in the water phase were mainly composed of glucose. The obtained glucose concentration, 702 mg/L was then fermented at 36 °C for 24 hours by Saccharomyces cerevisae (yeast) to ethanol. Maximum yield of ethanol production was 0.105 g/g glucose, which was 17.7% of theoretical yield. Hydrolysis with Sub-CW showed the potential to decompose the cotton textile into simple sugar while keeping sugar degradation to minimal phase and the possibility of complete conversion of cotton textile waste to ethanol via Sub-CW and fermentation.